Personification in Leila S. Chudori's Novel Homecoming - Annisa Widya Utami (Institute of Multidisciplinary Research and Community Service, 2022)
This research focuses on research into personification figures of speech found in sentences in the novel Pulang by Leila S. Chudori. A personification figure of speech is a figure of speech that depicts inanimate, inanimate objects as if they have human-like characteristics and abilities. The Pulang novel by Leila S, Chudori tells about the struggles of Indonesian youths who were also former politicians (Hananto, Alam, Dimas Suryo, Vivienne, Risjaf, Tjai Sin Soe, Bimo, Kenanga, Rinita, Lintang and Nugroho) in saving their friends. friends in Indonesia who were kidnapped, shot, and imprisoned in the September 30, 1998 tragedy. The study of personification in this study was carried out so that readers can better understand and appreciate all forms of beauty in stories packaged in personification as well as increase readers' understanding of personification figurative language. This research uses a descriptive qualitative method. This method can describe/detail the use of personification figures of speech in the novel Pulang by Leila S. Chudori. There were five data in this study which were analyzed from conversations and narratives contained in the novel Pulang by Leila S. Chudori. From the results of the analysis, personification figures of speech are dominant in chapters 3 and 7 Keywords: Personification, Pulang Novel by Leila S. Chudori